(3TQM GHf GdfGXes - (3GdWGFj GdCfOdSj, GHf GdnqfGpXe, HOQ GdOjf, eMeO Hf eMeO Hf YHO Gddg Hf eGdc, J (B686 (3g`s ((3GdchaIs)
(3ChdgG (B:s
(3MeOG ddg SHMGfg HeG dg ef GdeMGeO (B.. (3aEfj CPcQ aj gPG GdcJGH CQLhRI hGdOj aj Yde GdfMh GdeSeGI HGdNdGUI eQUYgG HTQM jMd efgG GdeTcd hjaJM ef CHhGHgG cd ebad hLGfHJ ajg GdEjLGR GdeNd hGdGWfGH Gdeed MQUG Ydi (B...s
(3BNQgG (B:s
(3hanqc CanYd aj GdJYoqLH GdJRe (B... (3hGdJRe GdEOZGoe CjVkG aj gode deG aQZ ef GdcdGe Yf GdeLRhe hGdCeQ TQY aj HjGf Mce CaYd aj GdJYLH hCfg eachc CHOG HNdGa ZjQg ef CeKdI GdCeQ CMHH Edi RjO HYeQh hGTOO HHjGV hLg RjO (B.. (3gPG BNQ eG JVefJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdfMhs